2019
DOI: 10.1016/j.ebiom.2019.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Salsalate, but not metformin or canagliflozin, slows kidney cyst growth in an adult-onset mouse model of polycystic kidney disease

Abstract: BackgroundMultiple preclinical studies have highlighted AMP-activated protein kinase (AMPK) as a potential therapeutic target for autosomal dominant polycystic kidney disease (ADPKD). Both metformin and canagliflozin indirectly activate AMPK by inhibiting mitochondrial function, while salsalate is a direct AMPK activator. Metformin, canagliflozin and salsalate (a prodrug dimer of salicylate) are approved for clinical use with excellent safety profile. Although metformin treatment had been shown to attenuate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 58 publications
5
68
1
3
Order By: Relevance
“…Similarly, we found that AMPK activation via Metformin had no effect on cell proliferation. Although Metformin was suggested to have beneficial effects on disease progression 27 , the effect of Metformin on cell proliferation and cyst growth has been brought into question by another recent study 28 . Additionally, differences in concentration or time frame of compound treatment could account for the lack of activity observed.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we found that AMPK activation via Metformin had no effect on cell proliferation. Although Metformin was suggested to have beneficial effects on disease progression 27 , the effect of Metformin on cell proliferation and cyst growth has been brought into question by another recent study 28 . Additionally, differences in concentration or time frame of compound treatment could account for the lack of activity observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, although our PKD mice and PCK rats seem to respond differently to pioglitazone, several other data do suggest an overlap in important PKD related mechanisms. Inflammatory processes, increased proliferation and altered fatty acid metabolism are all shared between PCK rats and our PKD mice 44,47 . At the molecular level, mTOR and cAMP related signalling has been shown to drive cyst growth in many models of PKD and both the PCK rat and our PKD mice are capable to respond to inhibitors of those signalling pathways (i.e.…”
Section: Discussionmentioning
confidence: 87%
“…To investigate the effects of a combination treatment in vivo, we performed a preclinical study with our adult-onset PKD mouse model (iKspCre-Pkd1 del , Fig. 2c) 43,44 . Pkd1 gene deletion was induced at post-natal (PN) days 18 & 19 via administration of tamoxifen via oral gavage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum metformin was measured using liquid chromatographytandem mass spectrometry, as described in ref. 45 .…”
Section: Methodsmentioning
confidence: 99%